Sinergi edukasi dan tindakan sosial: Gizi ceria sebagai upaya mendorong pola hidup sehat melalui pemahaman gizi yang tepat - Mudawiyah, Hidayatul (Maliki Interdisciplinary Journal, 2025)
"Gizi Ceria" is an innovative program from the Adiwangsa Community Health Center (KKM Adiwangsa) as a form of community service in the field of nutrition. Implemented on February 19, 2025, in Bandar Kidul Village, this program aims to raise public awareness about the importance of balanced nutrition and the use of local foods. Activities included counseling, health checks, and the distribution of moringa leaf pudding as an example of a nutritious product. The positive response from residents demonstrated the program's long-term potential in fostering healthy lifestyle habits and utilizing local food resources sustainably. In addition to providing nutrition education, this program also encouraged active community involvement through question-and-answer sessions and hands-on practice of moringa leaf-based food processing. These activities were designed to strengthen participants' understanding of the nutritional content and health benefits of local foods. With a participatory approach, the community not only received information but also acquired skills that can be applied in their daily lives. Going forward, "Gizi Ceria" is expected to become a model of community service that can be replicated in other regions to support the achievement of food security and improve national nutritional status.